TEKNOLOGI DALAM PEMBELAJARAN IPS: ANALISIS KETERAMPILAN DIGITAL BAGI CALON GURU MADRASAH IBTIDAIYAH - Aslamiah, Syaibatul; Sa’adah, Nelly (STIT Ibnu Rusyd Tanah Grogot, 2024)
With the increasingly convergence of the boundaries between humans, machines, and other resources, the development of information and communication technology has a significant impact on various aspects of life, including the field of education in Indonesia. To answer these challenges, digital skills are needed by the teachers themselves, with the preparation of digital skills in such a way that time is also needed for preparation, therefore students as prospective teachers need to prepare digital skills before entering the school environment. This study uses a qualitative research approach of a qualitative-descriptive research design. The purpose of the study is to identify the level of mastery of digital skills of prospective Madrasah Ibtidaiyah teachers, as well as to identify the urgency of mastering digital skills for prospective madrasah ibtidaiyah teachers in the context of Social Sciences learning at Madrasah Ibtidaiyah. The data collection technique used is interviews. The results of this study show that the level of mastery of digital skills of prospective teachers is in the